Durability of hybrid clinch-bonded steel/aluminum joints in salt spray environment. Issue 9 (December 2016) - Calabrese, L.; Galtieri, G.; Borsellino, C.; Bella, G.; Proverbio, E.
Abstract In this work, hybrid aluminum alloy/steel joints by combining clinching and bonding processes were realized. Furthermore, we investigated how the presence of an adhesive interlayer can influence the performance of hybrid joints when exposed in salt spray environment up to 15 weeks of ageing. The durability of steel/aluminum joints is a well-known problem, in particular for steel-reinforced aluminum frames, in aggressive environmental conditions. The aluminum alloy/steel joints were made by interposing an adhesive layer (modified silane (MS) polymer) and clinching before the polymerization has taken place. A proper design of experiment has been carried out, followed by the ANOVA of the results. The experimental results of long-term ageing tests (ASTM B 117) evidenced that the corrosion degradation phenomena influenced significantly the mechanical performance of the hybrid joints. By comparison with the pure mechanical clinching joints, in the same configurations studied in a previous work, the shear load trends are similar. The presence of the flexible adhesive layer gave a significant advantage on resistance to a corrosive attack but little influences the mechanical strength.